PENGARUH LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR TEKSTIL DAN GARMENT YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Anita Novianti; Rudy Rudy (JURNAL MITRA MANAJEMEN, 2023)
The purpose of this research is to find out and analyze the effect of liquidity variables on profit growth, to know and analyze the influence of solvability variables on profit growth, to know and analyze the influence of profitability variables on profit growth and to know and analyze the effect of liquidity, solvency and profitability variables on profit growth. The research method used is the quantitative method and is in the form of secondary data, where the data in this study were obtained based on the financial reports contained on the IDX. The results of this study indicate that liquidity has a negative and significant effect on profit growth, solvency has a negative and significant effect on profit growth, profitability has a negative and insignificant effect on profit growth, and there is a significant effect simultaneously on liquidity, solvency and profitability on growth. profit. Keywords : Influence, profitability, liquidity, solvency, manufacturing, textiles and garments